Penerapan Raspberry Pi untuk Pengukuran Jarak Jauh terhadap Potensi Energi Angin - Ferry Faisal; Eko Mardianto; Taufik Muzakir (Politeknik Negeri Pontianak, 2018)
This research develop a web-based remote measurement system using Raspberry Pi to measure wind speeds. The specific objective to be achieved is to obtain the data of the average wind speed measurement (daily, weekly and monthly) for the design needs of the Wind Power Generation. The methodology used in this research is focused on experimental methodology and software development. The results of the experimental methodology and software development produce a good design of web-based remote measurement system that worked correctly.